Mechatronic Test Bench Used to Simulate Wind Power Conversion to Thermal Power by Means of a Hydraulic Transmission - Victor Constantin; Ionela Popescu; Mihai Avram (Technologies, 2025)
The work presented in this paper discusses the steps taken to design, implement, and test a mechatronic test stand that uses historical wind power data to generate thermal power that could be used by small-to-medium consumers. The work also pertains to usage in areas where large wind turbines could not be installed due to space restrictions, such as highly populated areas. A rotor flux control (RFC) speed-controlled 2.2 kW AC motor was used to simulate the action of a wind turbine on a 6 cm3 hydraulic pump. The setup allows for a small form factor and a much lighter turbine to be installed. The paper describes the schematic, installation, usage, and initial results obtained using a hydraulic test stand developed by the authors. The initial work allowed us to obtain different temperatures of the hydraulic oil, up to 60 °C, over a period of 30 min, for various pressures and flow rates, thus confirming that the system is functional overall. Further work will elaborate on the effect of different wind patterns on the setup, as well as provide an in-depth study on a use case for the system.